A study on the allelopathic tolerance of garden pea varieties to Sorghum halepense (L.) Pers. extracts - Georgieva, Natalia; Kosev, Valentin; Kalapchieva, Slavka (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
The present research study identified garden pea varieties with pronounced tolerance to the allelopatic action of Sorghum halepense. Nine varieties were selected to study the effects of shoot and root weed biomass, applied in three extract concentrations (1, 5 and 10%), on seed germination and initial germ growth. A variance analysis of data revealed significant influence (p
Keywords: allelopathy; weeds; Pisum sativum; Sorghum halepense